Stem cell therapy and tissue engineering for correction of congenital heart disease - Avolio, Elisa; Caputo, Massimo; Madeddu, Paolo (Frontiers in Cell and Developmental Biology, 2015)
This review article reports on the new field of stem cell therapy and tissue engineering and its potential on the management of congenital heart disease. To date, stem cell therapy has mainly focused on treatment of ischemic heart disease and heart failure, with initial indication of safety and mild-to-moderate efficacy. Preclinical studies and initial clinical trials suggest that the approach could be uniquely suited for the correction of congenital defects of the heart. The basic concept is to create living material made by cellularized grafts that, once implanted into the heart, grows and remodels in parallel with the recipient organ. This would make a substantial improvement in current clinical management, which often requires repeated surgical corrections for failure of implanted grafts. Different types of stem cells have been considered and the identification of specific cardiac stem cells within the heterogeneous population of mesenchymal and stromal cells offers opportunities for de novo cardiomyogenesis. In addition, endothelial cells and vascular progenitors, including cells with pericyte characteristics, may be necessary to generate efficiently perfused grafts. The implementation of current surgical grafts by stem cell engineering could address the unmet clinical needs of patients with congenital heart defects.